Dominance in wintering Anatinae: potential effects on clutch size and time of nesting - Hepp, Gary R (Wildfowl, 1984)
The author proposes that delayed nesting and reduced clutch size of female Anatinae breeding for the first time may be caused by social factors, occurring outside the breeding season, which affect development of nutrient reserves.